Uteroferrin has N-asparagine-linked high-mannose-type oligosaccharides that contain mannose 6-phosphate. - Baumbach, G A (1984)
Uteroferrin is an iron-containing, progesterone-induced, acid phosphatase that is secreted in large amounts by the uterine endometrium of pigs. During pregnancy, it transports iron across the chorioallantois (placenta) for use in fetal hematopoiesis. In this paper, it is reported that uteroferrin synthesized by cultured endometrial explants possesses N-linked, high-mannose, oligosaccharide chains that contain 6- phosphomannose units. The latter is regarded as a possible recognition marker whereby acid hydrolases are targeted to the lysosome. On uteroferrin, however, the majority of the phosphate is in single diester linkages between the mannose and a covering N-acetylglucosamine. It is suggested that uteroferrin is a lysosomal enzyme that has assumed a role in iron transport and metabolism and is secreted because the covering N-acetylglucosamine is not removed.